Quantitative carcass traits of Charolais steers, slaughtered with different weights - Restle, João; Keplin, Luís Antonio da Silveira; Vaz, Fabiano Nunes (Pesquisa Agropecuaria Brasileira, 1997)
The influence of different slaughter weights on carcass quantitative traits of finished confined Charolais steers was studied. Eighteen steers, 30 month-old and initial weight of 297 kg, were distributed in the following treatmens: T420 slaughter weight=420 kg; T460 slaughter weight = 460 kg; and T500 slaughter weight=500 kg; the effective slaughter weights were 421 kg, 461 kg and 495 kg, respectively. Dressing percentage was 50.7% (T420), 52.7% (T460) and 52.4% (T500). The lowest conformation score was observed for T420 carcasses, and the Longissimus dorsi area per 100 kg carcass weight decreased as slaughter weight increased (31.6 cm2, 30.3 cm2 and 27.1 cm2). Fat thickness of T500 (5.4 mm) was higher than T420 (2.4 mm) and T460 (2.6 mm). As steers slaughter weight increased, the fat percentage (15.5%, 16.5% and 19.4%) increased and bone percentage (16.4%, 13.5% and 13.3%) decreased. T460 steers showed higher muscle percentage (71.5%) than T420 steers (68.1%). No difference was observed for forequarter percentage (T420=36.7%, T460=36.2% and T500=36.8%); saw cut percentage was higher in the T460 (50.4%) and T420 (50.1%) than T500 (47.5%). This treatment showed higher side cut percentage (15.7%) than T420 (13.2%) and T460 (13.4%). No significant differences were observed for carcass length, and leg arm perimeter and cushion thickness.